Pengelolaan Deep Learning (Studi Kualitatif Di SD Negeri 84 Bengkulu Selatan Kecamatan Pino Raya Kabupaten Bengkulu Selatan) - Yuliana, Septi; Danim, Sudarwan; Connie , Connie (Manajer Pendididikan, 2025)
This study aims to describe the planning process of deep learning management at Elementary School Negeri 84 Bengkulu Selatan which includes planning, implementation, evaluation, supporting and inhibiting factors, and the impact of deep learning management on learning outcomes, motivation, and the development of higher order thinking skills. The method used is descriptive qualitative with interview, observation and documentation techniques. Data analysis was conducted using Miles and Huberman's interactive model consisting of data reduction, data presentation, and data verification. The results of the study were: 1). Planning is done through teacher meetings, learning objectives are adjusted to the independent curriculum, contextual materials, and flexible learning time for exploration and discussion.2). The implementation of deep learning uses project-based learning, inquiry, group discussions, experiments, and presentations. Students are actively involved through problem solving and collaboration. 3). Evaluation uses portfolios, rubrics, observation, and self-assessment. Results are used for feedback and learning improvement..4). The management of deep learning is supported by the principal, teachers, adequate facilities, parents' involvement, the obstacles are time constraints, lack of teacher training, and differences in students' abilities. 5). Improve learning outcomes, motivation, creativity, and students' critical thinking and problem solving skills.